Bad Kitty goes to the vet - Bruel, Nick (Square Fish, An imprint of Macmillan : Roaring Brook Press New York, 2017)
"Even the best bad kitties can get sick, and when it happens, it means just one thing: a visit to the vet!"-- Provided by publisher